Self-assessment of hearing quality of traffic policemen working in Dharan-Biratnagar corridor - Ghimire, A; Niraula, S R; Shrestha, A; Jha, N (Journal of Chitwan Medical College, 2017)
The automobiles are an important source of not only air pollution but also of a significant proportion of noise pollution. The traffic police engaged in controlling traffic, particularly at heavy traffic junctions, belong to the high risk group to be affected by the health hazards of noise and air pollution. To assess the hearing quality of traffic policeman towards the health effects caused by noise pollution and their practices on the use of protective measures. The present cross-sectional study was carried out among 78 traffic policemen working in Dharan-Biratnagar corridor. The questionnaire included questions regarding the self- assessment of the traffic policeman about their hearing ability, past and present exposure to loud sound produce by automobiles and the use of personal protective devices. Ethical clearance was obtained from ethical board of BPKIHS, Verbal consent was taken from all the study subjects. Finding of this study shows that most of the respondents were between the ages of 25 to 29 years (33.3%), similarly 26% were under noise exposure since more than 10 to 14 years and 34.6% had exposure of noise 10 to 15 hours per day. Their self-assessment of hearing ability shows that 6.4% traffic policemen usually missed a lot when conversing with someone on phone, while 9% reported similar condition while talking to someone in a crowd and 23.1% reported that while watching television or while listening radio they usually kept the sound louder to hear properly. The study also revealed that the traffic police, in general do not use any personal protective equipment (92.3 %) and the non-availability of the PPEs is the common reasons for it. The self-assessment of hearing by traffic policemen suggests that most of the traffic policemen have normal hearing. However, a systematic study with audiometry of these subjects is recommended.